A Literature Review Study of the Role of Family Education in Minimizing Klitih Crime and Moral Decadence in Yogyakarta - Choirul Muna (Muslim Education Review, 2024)
The recent klitih case in Yogyakarta province is a result of the lack of the parents’ role in educating their children, and moral decadence. This klitih case has become a public concern because it endangers human lives. The need for comprehensive intervention to minimize this type of crime becomes a necessity. The hope is to create peace, comfort, tranquility and a prosperous life for the people in Yogyakarta. This study aims to explore the importance of the role of the family in educating children to minimize crime and moral decadence in the province of the Yogyakarta Special Region. This research is descriptive-qualitative, with the main approach using a literature review as a data-mining tool. The results show there are background factors causing klitih crime. There are also roles parents can play in educating their children and minimizing moral decadence in Yogyakarta. This study recommends parents be more intense in monitoring the activities of their children. Lastly, this study also recommends involving religious and moral values of the culture to foster a child’s thinking sense to avoid harmful, deviant behavior and crime.